PENGARUH STRATEGI THINK TALK WRITE (TTW) BERBANTUAN MEDIA GAMBAR TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS X MIA MAN PASIR PENGARAIAN TAHUN PEMBELAJARAN 2014/2015 - Nasution, Hilman; Lestari, Rena; Lubis, Riki Riharji (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The aims of this study was to determine learning outcomes of MAN Pasir Pengaraian students Class X MIA with Think Talk Write (TTW) method by using pictures as media. This was an quasi-experimental study. Sample were the students of class X MIA1 and X MIA2 MAN Pasir Pengaraian. Result showed that studying Biology on Protista subject by using TTW method and picture as media was better whith outusing TTW method and picture as media. The average value of experimental class was 76.85, meanwhile the control class was 60.34